Letters to the Paulaharjus from Ruija: The emergence of two writing cultures in Finnish among Kvens in the early twentieth century - Haataja, Daniel; Niiranen, Leena Mirjam (Nordic Journal of Linguistics, 2023)
Samuli Paulaharju was a Finnish ethnographer who visited the Kven minority in Northern Norway – Ruija – in the 1920s and 1930s. Together with his wife Jenny he collected ethnographic material among the Kvens, and corresponded frequently with some of them. Many wrote in Finnish, and most were self-taught writers. We focus on the orthography used by these writers who were writing in a multilingual environment. We identify two writing cultures, one associated with Old Literary Finnish and Early Modern Finnish, the other with Modern Written Finnish (MWF). The orthography used by the former is characterized by the use of b, d, g for p, t, k in native Finnish words, which we attribute to influence from Norwegian. By contrast, the orthography of the latter largely resembles the MWF of the time. However, both groups substitute t for d – a phenomenon found in Finland during the same time period – as well as occasionally use Norwegian characters.